Estrategia de comercialización de bicicletas de alto desempeño en el mercado internacional: análisis de caso Canyon-Alemania (2019)
In this paper analyzes the different marketing strategies used by representative brands of bicycles in the Colombian market. The behavior of the world sector in terms of production, export and import and the activity in the Colombian market are also analyzed. The analyzed information presents the differences in the structures of distribution channels and distribution strategies. A marketing strategy for high performance bicycles is proposed for the Canyon company in the Colombian market based on the problems and needs of consumers.